Economic cultural influence: Effect on headquater - subsidiary management Slovenia and three longstanding EU countries - Rune Gulev (Journal for East European Management Studies, 2006)
This study systematically investigates two dimensions through which economic culture can be measured and compared between four EU countries: Slovenia, Germany, Austria and Denmark, and projects their respective impacts onto the management of an international Headquarter - subsidiary relationship. The results confirm that there exists considerable differences in economic cultures between the four countries and that the differences have a direct impact on international management. Most notably, a strong positive correlation was found between the highly subordinate driven cultures of Denmark and Austria to have a bias towards two-way knowledge flows. Mixed results were found on capitalistic driven cultures impact on control mechanisms and use of motivational factors. – – Diese Studie untersucht systematisch zwei Maße, durch die die ökonomische Kultur von vier EU-Ländern (Slowenien, Deutschland, Österreich, Dänemark) gemessen und verglichen werden kann. Darüber hinaus werden ihre Auswirkungen auf das Management des Verhältnisses zwischen dem internationalen Hauptsitz und der Tochterniederlassung aufgezeigt. Die Resultate bestätigen, dass beträchtliche Unterschiede bezüglich der ökonomischen Kulturen zwischen den vier Ländern bestehen und dass die Unterschiede eine direkte Auswirkung auf das internationale Management haben. Vor allem wurde eine stark positive Korrelation zwischen den stark Niederlassungs-orientierten Kulturen Dänemarks und Österreichs gefunden, die dadurch auch eine deutliche Einstellung gegen wechselseitige Wissensflüsse aufwiesen. Gemischte Ergebnisse wurden gefunden hinsichtlich des Einflusses von kapitalistisch orientierten Kulturen auf Kontrollmechanismen und dem Einsatz von motiviationalen Faktoren.
Keywords: 650; economic culture; subsidiary management; multinational companies; internationalization; EU